2021
DOI: 10.1038/s41529-021-00191-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of ancient Maya carved tuff stone at Copan and its bacterial bioconservation

Abstract: Much stone sculptural and architectural heritage is crumbling, especially in intense tropical environments. This is exemplified by significant losses on carvings made of tuff stone at the Classic Maya site of Copan. Here we demonstrate that Copan stone primarily decays due to stress generated by humidity-related clay swelling resulting in spalling and material loss, a damaging process that appears to be facilitated by the microbial bioweathering of the tuff stone minerals (particularly feldspars). Such a weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The precipitation of calcium oxalate and calcium carbonate is influenced by fungal growth, as well as environmental conditions. Therefore, it is necessary to explain the precipitation process for calcium oxalate and calcium carbonate to provide a solid basis for subsequent microbial control and enable its use as a biotechnological tool for heritage protection [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The precipitation of calcium oxalate and calcium carbonate is influenced by fungal growth, as well as environmental conditions. Therefore, it is necessary to explain the precipitation process for calcium oxalate and calcium carbonate to provide a solid basis for subsequent microbial control and enable its use as a biotechnological tool for heritage protection [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biofilms affected the contact angle of a surface by changing the surface chemistry, roughness and re-entrant topography (Epstein et al, 2011;Tanaka et al, 2019). Increased water contact angles were also examined due to carbonatogenic bacteria (Elert et al, 2021) and Bacillus subtilis (Epstein et al, 2011). Polson et al (2002Polson et al ( , 2010 detected a change in wettability on quartz by a bacterial-fungal consortium that made the surface hydrophobic, while an algal consortium left the surface hydrophilic.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, mineralogical analysis of a range of building stone types showing surface flaking and scaling (i.e., detachment of sub-mm to mm-thick surface layers totally independent of the stone structure), exfoliation (i.e., detachment of multiple cm-thick surface layers along stone bedding/structural planes), spalling (i.e., detachment of up to cm-thick layers sub-parallel to the stone surface), delamination (i.e., detachment of multiple thin stone layers sub-parallel to the stone surface), or contour scaling (i.e., detachment of mm-to cmthick surface layers following the contour of stone surface features) (names of weathering forms after Vergés-Belmin [43]) (Fig. 1), revealed that, typically, they included clay minerals, normally in small quantities (commonly < 10 wt%) [8,9,[44][45][46][47][48][49][50][51].…”
Section: The Importance Of Clay Swelling Damagementioning
confidence: 99%
“…Importantly, such stones displayed a significant hygric and/or hydric expansion (i.e., expansion in contact with vapor or liquid water, respectively), which led to the conclusion that clay swelling/shrinkage following wet-dry cycles had to be involved in their degradation [8,9,52,53]. Stone expansion is easily quantified in the laboratory using a linear variable differential transformer (LVDT), which measures changes in the dimension of a stone sample (i.e., free swelling strain ε = Δl/l, where Δl is the length increase of a sample with initial length l) with an accuracy of (at least) ± 1 μm upon changes in relative humidity or upon immersion in water [10,51]. Such measurements showed that the free swelling strain of clay-containing stones could reach values of up to ~ 0.01 (i.e., 1% = 10 mm/m) [50], and, in extreme cases, values of up to ~ 0.05 [9,50].…”
Section: The Importance Of Clay Swelling Damagementioning
confidence: 99%